Anticoagulation increases alveolar hemorrhage in mice infected with influenza A. Issue 24 (21st December 2016) - Tatsumi, Kohei; Antoniak, Silvio; Subramaniam, Saravanan; Gondouin, Bertrand; Neidich, Scott D.; Beck, Melinda A.; Mickelson, Jacqueline; Monroe, Dougald M.; Bastarache, Julie A.; Mackman, Nigel
Abstract: Influenza A virus infection is a common respiratory tract infection. Alveolar hemorrhage has been reported in patients with influenza pneumonia and in mice infected with influenza A. In this study, we investigated the effect of two anticoagulants on alveolar hemorrhage after influenza A virus (IAV) infection of wild‐type mice. Wild‐type mice were anticoagulated with either warfarin or the direct thrombin inhibitor dabigatran etexilate and then infected with a mouse‐adapted influenza virus (A/Puerto Rico/8/34 H1N1). Alveolar hemorrhage was assessed by measuring hemoglobin levels in the bronchoalveolar lavage fluid (BALF). We also measured vascular permeability and viral genomes in the lung, as well as white blood cells, inflammatory mediators, and protein in BALF. Survival and body weight were monitored for 14 days after influenza A infection. In infected mice receiving either warfarin or dabigatran etexilate we observed decreased activation of coagulation in the BALF and increased alveolar hemorrhage. Warfarin but not dabigatran etexilate increased vascular permeability and mortality of influenza A‐infected mice. Anticoagulation did not affect levels of influenza A genomes, white blood cells, inflammatory mediators, or protein in the BALF. Our study indicates that systemic anticoagulation increases alveolar hemorrhage in influenza A‐infected mice. Abstract : Anticoagulation of wild‐type mice with the vitamin K antagonist warfarin (2 μ g/mL; W2 or 4 μ g/mL; W4) or the direct thrombin inhibitor dabigatran etexilate (DE; 10 mg/g chow) increased alveolar hemorrhage after influenza A virus infection. We also observed increased mortality in wild‐type mice receiving warfarin but not dabigatran etexilate.